Synthesis and Characterization of Montmorillonite Membrane for Nickel and Zink Metals Filtration in Electroplating Liquid Waste - Hidayah, I. (Universitas Negeri Yogyakarta, 2020)
The application of ceramic membrane technology has been applied in water treatment. The montmorillonite used was analyzed by XRD and showed typical montmorillonite peaks at 2Î¸ 7.49o, 28.07o, 35.75 o, 40.73o, 49.14o dan 67.03o. Montmorillonite membrane was made by the process of dry pressing.PVA in montmorillonite is expected to function as a binder agent. The result variation on PVA composition 0%, 1%. 2%, 3% and 4%, show the flux value that increased with the adition of PVA composition. The montmorillonite membrane with a 4% PVA composition a result greatest flux and porosity values compared to other compositions. The resulting flux value is 1596.5679 L/m2.h and porosity 20.9477%. SEM-EDXtest result showed montmorillonite membrane is a porous membrane that is spread and evenly distributed but the resulting pore is not uniform. Montmorillonite membrane rejection of nickel metal was 55.5352% dan zink metal was 37.8614% with a 40-minute filtration process.